Variant spectrum of von Hippel–Lindau disease and its genomic heterogeneity in Japan - Tamura, Kenji; Kanazashi, Yuki; Kawada, Chiaki; Sekine, Yuya; Maejima, Kazuhiro; Ashida, Shingo; Karashima, Takashi; Kojima, Shohei; Parrish, Nickolas F; Kosugi, Shunichi; Terao, Chikashi; Sasagawa, Shota; et al. (Human molecular genetics, 2023)
Abstract Von Hippel–Lindau (VHL) disease is an autosomal dominant, inherited syndrome with variants in the VHL gene, causing predisposition to multi-organ neoplasms with vessel abnormality. Germline variants in VHL can be detected in 80–90% of patients clinically diagnosed with VHL disease. Here, we summarize the results of genetic tests for 206 Japanese VHL families, and elucidate the molecular mechanisms of VHL disease, especially in variant-negative unsolved cases. Of the 206 families, genetic diagnosis was positive in 175 families (85%), including 134 families (65%) diagnosed by exon sequencing (15 novel variants) and 41 (20%) diagnosed by multiplex ligation-dependent probe amplification (MLPA) (one novel variant). The deleterious variants were significantly enriched in VHL disease Type 1. Interestingly, five synonymous or non-synonymous variants within exon 2 caused exon 2 skipping, which is the first report of exon 2 skipping caused by several missense variants. Whole genome and target deep sequencing analysis were performed for 22 unsolved cases with no variant identified and found three cases with VHL mosaicism (variant allele frequency: 2.5–22%), one with mobile element insertion in the VHL promoter region, and two with a pathogenic variant of BAP1 or SDHB. The variants associated with VHL disease are heterogeneous, and for more accuracy of the genetic diagnosis of VHL disease, comprehensive genome and DNA/RNA analyses are required to detect VHL mosaicism, complicated structure variants and other related gene variants.